PENGARUH PENGELUARAN DANA PROGRAM KEMITRAAN USAHA DAN RELAWAN TERHADAP PENGHIMPUNAN DANA ZAKAT (Studi Lembaga Amil Zakat Baitulmaalku Karawang Periode 2017 - 2019) - 'Ainulyaqin, Muhammad Hamdan; Lutin, Hendro (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
The very positive potential of zakat in Indonesia triggers competition betweem many amil zakat institutions to gain muzakki‟s trust. In zakat management institutions the activities of collecting (fundraising) zakat funds are very important for amil zakat institutions to cary out institutional activities. This study aims to analyze the effect of business and volunteer partnership programs on the collectionbof zakat funds. Volunteer and business partnership program as an independent variable and zakat fund collection as the dependent variable. The object of research at the Baitulmaalku Karawang amil zakat intitute. The research method uses quantitative methods of data collection with secondary data in the form of financial reports. The subject of this research is the Baitulmaalku Karawang amil zakat institution. The number of samples is 36, the analysis method used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The analysis results obtained partially, the business partnership program has a value of 4,214 and a significance value of 0,00 and volunteeers have a t value of 1,616 and a significance value of 1,16. simultaneously get the F value count 122,528 and a significance value of 0,00. The business partnership program has a positive and significant effect on the collection of zakat fund. Whilw volnteers do not have a positive and significant effect on the collection of zakat funds. Simultaneously partnership of business and volunteers affects the collection of zakat funds.